2018
DOI: 10.1097/ncq.0000000000000278
|View full text |Cite
|
Sign up to set email alerts
|

Post–Hospital Medication Discrepancies at Home

Abstract: The purpose of this study was to evaluate the occurrence of medication discrepancies during transitional care home visits and the association with emergency department (ED) visits. Using secondary data analysis, the relationships between in-home medication discrepancies and 30- and 90-day ED utilization were examined. For every in-home medication discrepancy, the odds of being admitted to the ED within 90 days increased by 31%. This brief intervention could add a valuable component to post-hospital transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…Patients included in this study were 65 years or older (median 74 years; IQR 69–80) as in comparable studies, 2,6,10 while other studies also included younger patients. 35,79 The frequency would be expected as higher in studies of older patients, as polypharmacy is high in this group. 21,22 The inclusion of OTCs in this study probably increased the number of discrepancies found; therefore, data are presented separately for regular medications, as-needed medications and OTCs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Patients included in this study were 65 years or older (median 74 years; IQR 69–80) as in comparable studies, 2,6,10 while other studies also included younger patients. 35,79 The frequency would be expected as higher in studies of older patients, as polypharmacy is high in this group. 21,22 The inclusion of OTCs in this study probably increased the number of discrepancies found; therefore, data are presented separately for regular medications, as-needed medications and OTCs.…”
Section: Discussionmentioning
confidence: 97%
“…At discharge, 14–84% of patients experience at least one medication discrepancy. 110 Medication discrepancies after discharge can lead to increased hospital visits 6,7,11 or preventable adverse drug events. 12 Older patients are especially at risk, as polypharmacy, comorbidities, and longer hospital stays are associated with increased medication errors.…”
Section: Introductionmentioning
confidence: 99%
“…The unplanned return to emergency departments within 30 days of hospital discharge is rarely investigated, and the studies developed until now, alert to the importance of widening the investigations about this period, in order to increase knowledge as to the acute care based on hospitals of patients with recent discharge. 4 , 5 , 8 , 18 Analysis of the care given during hospitalization, considering only hospital readmission, does not afford an integral view of the acute care given, and limits the development of actions in favor of improved transition of care, especially of the mature patients.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of medication errors and adverse drug events among ambulatory patients in the community may be due to medication discrepancies or changes in medications that take place during transition of care. A medication discrepancy is the lack of agreement between different medication regimens during transition from acute care to post-acute care, 9 while transition of care has been identified as one of the key action areas by the World Health Organization (WHO) Global Patient Safety Challenge on Medication Safety.…”
mentioning
confidence: 99%
“…Medication discrepancies place patients at risk of medication error and adverse drug events, as these patients have 31.0% higher chances of being readmitted within 90 days of hospital discharge 9 . Recent data have shown that one third of visits to the emergency department of a teaching hospital in Malaysia were medication-related 10 …”
mentioning
confidence: 99%